ANALISIS PENILAIAN KINERJA PORTOFOLIO SAHAM DENGAN MENGGUNAKAN METODE SHARPE MEASURE DAN TREYNOR MEASURE PADA SAHAM-SAHAM INDEKS SEKTORAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2008-2010 - Atik Budi Paryanti; Sri Lestari (STIKOM CKI, 2016)
The study of the research is about performance assesment analysis of stock portofolio evaluated by using Sharpe adn Treynor method in active stocks traded consistencely over three years, and those stocks represent industrial sectors classified in Indonesia Stock Exchange. Besides, the aim of the use of both methods in to find out result of measurement consistency comparison from each models in measuring stock portofolio performance in Indonesia Stock Exchange is that it can be found whether there is a model used as direction for investor in measuring stock portofolio performance as investation portofolio.According to the result of independent t-test, it can be explained that t-score is 3,230 and sig. Is 0,021(< 0,05), it can be concluded that there is difference between two portofolio performance, Sharpe and Treynor method, over the period of the research. The result of both method shows that measurment of Sharpe method is higher than measurment of Treynor method (0,3833 > 0,1285). Moreover, this result shows that investors and investors managers in evaluating portofolio performance view that Sharpe method is more approriate because this method is more effective in measuring or assessing stock portofolio performance that can be minimalized in whole risk sistematically or insistematically existed in stock portofolio combination.Key words : Optimal portofolio, Sharpe Measure, Treynor Measure.